Identifying factors that affecting the status of road accident in Malaysia: multinomial logistic regression approach / Ainul Hasanah Na’imuddin - Na’imuddin, Ainul Hasanah (Univrsiti Teknologi MARA Cawangan Kelantan, 2015)
This project focuses on the factor that affecting the status of road accident in Malaysia. Chi-square test and multinomial logistic model are used in order to analyze the data. There are two objectives in this study which are to examine whether there presence significant relationship between dependent variable and independent variables, and to determine factors significantly influence status of road accident. The dependent variable in this study is the status of road accident while the independent variables used in this study are locality, road control, road type, road marking, type of area, surface condition and mechanical failure. Both data are in categorical. The scope of this study is all road users in Malaysia. The results of this study show that all variables have association with dependent variables using chi-square test while multinomial logistic regression shows all variables influence the status of road accident. After completing this study,it is well recommended that the law enforcement agencies should tighten the laws on the road. Other than that, Road Safety Council and other Non-Government Organization should organize more educational exhibition or talk about road safety to students and publics